SUCCESS FACTORS ON THE IMPLEMENTATION OF CERTIFICATION FOR GREEN PROJECT MANAGER (GPM) IN MALAYSIA - Mohd Saiful Rahim, Nur Halimah; Ismail, Zulhabri; Mohd Nordin, Rumaizah (Journal of Surveying, Construction and Property, 2020)
The paper aims to establish the success factors in promoting certified Green Project Managers (GPM) in Malaysia’s construction projects. A set of self-administered questionnaires through snowball sampling method was used to retrieve information among 30 respondents within various backgrounds which include project directors, general managers and project managers. Based on the analysis using Statistical Package for the Social Sciences (SPSS), this research has discovered that the main reason GPMs are highly needed in Malaysia’s construction industry is to ensure a successful delivery of green development goals. Nevertheless, this research found a number of challenges in promoting certified GPM, which include limited training for project managers that incorporates sustainability elements. This research found that training is significant to equip them with the necessary skills and knowledge towards becoming certified GPM to date, a private sector organization known as Bridget is the sole provider of specific training for GPM in Malaysia. The respondents of this study are limited among project directors, general managers and project managers in the Klang Valley who are currently involved in green building projects. This paper fulfils the recognized need to study the success factors on the implementation of certification for Green Project Managers (GPM) in Malaysia.